Impact of Sex on Infection Risk in Patients with Systemic Lupus Erythematosus - R. Borrelli; S. Nicola; F. Corradi; I. Badiu; L. Lo Sardo; N. Rashidy; A. Quinternetto; M. Mazzola; F. Meli; E. Saracco; I. Vitali; S. Negrini; et al. (Bioengineering)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that exhibits considerable diversity in terms of both clinical and immunological manifestations. Since its female-to-male ratio is around 9:1, it is well recognized that systemic lupus erythematosus mostly affects women, especially those of childbearing age. There is a greater susceptibility to infections in adult patients with systemic lupus erythematosus (SLE) compared to the general population. However, only a small number of studies have attempted to analyze this risk using real-life data, and even fewer have successfully assessed the influence of sex. Materials and Methods: A retrospective study was conducted, enrolling patients and dividing them into two groups based on their biological sex. Infectious episodes were identified from medical records and categorized by severity. Patients were stratified according to disease duration and treatment received. Logistic regression analysis was used to calculate the odds ratio (OR), with a 95% confidence interval (CI) for the assessment of risk factors. Multivariable logistic regression was performed to adjust for potential confounders. Model fit was evaluated using the Hosmer–Lemeshow test, and interactions between variables were tested. Sensitivity analyses were conducted to assess the robustness of the findings. Results: A total of 119 patients (107 females and 12 males) were included in the analysis. No significant difference in age was found between sexes (t = −0.715, p = 0.487), but disease duration was significantly shorter in males (t = 3.35, p = 0.003). Logistic regression showed a significant association between male sex and infection risk (β = 0.9426, p = 0.05), with males having an almost sixfold higher probability of infection compared to females (OR 5.675, 95% CI: 1.4479–22.2477, p = 0.0127). Disease duration (β = 0.0250, p = 0.102) and smoking status (β = 0.4529, p = 0.078) were not statistically significant. Lastly, correlation analysis revealed a significant association between SS-A antibodies and infection rate (r = 0.291, p = 0.003). Conclusions: This study highlights a significant sex-based disparity in the risk of infections among SLE patients, with males being at a higher risk compared to females. The differences in the distribution of infections, such as the higher prevalence of pneumonia in males and urinary tract infections in females, suggest that sex-specific factors, including immunological and hormonal differences, may influence infection susceptibility. Our findings emphasize the need for tailored clinical management, with increased vigilance for infections in male patients, to improve prevention strategies and targeted therapeutic interventions in this subgroup.